2002
DOI: 10.1007/s00125-002-0888-4
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine enhances impairment of endothelium-dependent relaxation and guanosine cyclic monophosphate formation in aortae from diabetic rabbits

Abstract: Aims/hypothesis. Both diabetes mellitus and hyperhomocysteinaemia are risk factors for cardiovascular disease and are associated with impaired endothelial nitric oxide and with excess superoxide formation. To explore potential vasculopathic interactions between these risk factors, the effect of homocysteine on endothelium-dependent relaxation and cyclic GMP formation was investigated in aortae from diabetic rabbits. Methods. Rabbits were rendered diabetic by intravenous injection of alloxan. Six months later, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 37 publications
1
40
0
2
Order By: Relevance
“…Blood was sampled at sacrifice for plasma glucose. Urine was also monitored over the duration of diabetes for glucose, ketone bodies, and proteins with Multistix (Ames Division, Miles Laboratories, Stoke Poges, Buckinghamshire, United Kingdom) as previously described [11,29]. Any animals displaying ketonuria or proteinuria were excluded from the study.…”
Section: Induction Of Diabetes Dosing and Sample Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood was sampled at sacrifice for plasma glucose. Urine was also monitored over the duration of diabetes for glucose, ketone bodies, and proteins with Multistix (Ames Division, Miles Laboratories, Stoke Poges, Buckinghamshire, United Kingdom) as previously described [11,29]. Any animals displaying ketonuria or proteinuria were excluded from the study.…”
Section: Induction Of Diabetes Dosing and Sample Collectionmentioning
confidence: 99%
“…Ethical approval for the study had been obtained from the local Committee at the University of Bristol. Male New Zealand white rabbits (3 kg) were injected intravenously with alloxan (Sigma Chemical, Poole Dorset, United Kingdom) via the lateral ear vein at a stat dose of 65 mg/ kg [11,29]; and age-matched controls, with saline alone. The diabetic rabbits were fed ad libitum with SDS standard rabbit chow (SDS, Whitham, United Kingdom) and allowed free access to water.…”
Section: Induction Of Diabetes Dosing and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that high tHcy [10,11], low folate [12,13] and high g-GT [14] predict cardiovascular disease. It is suggested that association between tHcy and cardiovascular disease is stronger in diabetic patients than in non-diabetic subjects [15,16].In the present study we analyzed the association between these cardiovascular risk factors and adiponectin levels in male type 2 diabetic patients. Since insulin affects adiponectin [17] and tHcy [18,19], diabetic patients who are not subject to insulin therapy were studied.…”
mentioning
confidence: 93%
“…In addition, the increased susceptibility of diabetic subjects to hyperhomocysteinaemia may be secondary to an acceleration of glucose-induced oxidative stress on endothelial cells (Soedamah-Muthu et al, 2005). This hypothesis is supported by animal studies showing that homocysteine-induced endothelial dysfunction occurs much more readily in the presence of diabetes than in its absence (Schukla et al, 2002).…”
Section: Endothelial Cell Dysfunctionmentioning
confidence: 83%